Considerations on risk in water supply systems - Rak, Janusz; Stręk, Magdalena; Piegdoń, Izabela; Tchórzewska-Cieślak, Barbara (Instal, 2025)
Risk management methods are evolving from passive approaches to active ones. This occurs through the application of risk reduction, retention, or avoidance strategies. The main aim of this paper is to analyze selected aspects of risk related to the functioning of water supply systems. Examples of risk assessment and evaluation are presented. Both endogenous and exogenous threats are addressed. Safety is considered one of the key areas of knowledge, particularly in relation to the critical infrastructure of urban agglomerations, which includes water supply systems.